1985
DOI: 10.1136/jcp.38.3.281
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric studies of age related changes in normal human breast and their significance for evolution of mammary cancer.

Abstract: SUMMARY Ageing changes in the normal human female breast were studied to determine their significance for the evolution of mammary cancer. Employing the morphometric techniques of point counting and planimetry, objective quantitative measurements were made of the structure of the normal female breast in 58 subjects from the prepubertal to late postreproductive period. The relative amounts of epithelial and connective tissue varied with age, and the epithelial elements (combined lobular and extralobular) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 8 publications
5
62
0
4
Order By: Relevance
“…Tissue blocks were not available for every single xenograft, but, based on the samples we did look at, we feel we can be confident that each pool of RNA extracted from the multiple xenografts is derived from comparable proportions of stroma, epithelium and fat. The proportions of different cell types in the xenografts is in the range previously published for pre-menopausal women (Hutson et al 1985).…”
Section: Tissue Heterogeneitysupporting
confidence: 57%
See 1 more Smart Citation
“…Tissue blocks were not available for every single xenograft, but, based on the samples we did look at, we feel we can be confident that each pool of RNA extracted from the multiple xenografts is derived from comparable proportions of stroma, epithelium and fat. The proportions of different cell types in the xenografts is in the range previously published for pre-menopausal women (Hutson et al 1985).…”
Section: Tissue Heterogeneitysupporting
confidence: 57%
“…Genetic experiments on the rodent breast, especially during puberty, have highlighted the importance not only of the epithelium but interactions between these cells and other cell types within the breast, such as fibroblast, adipocytes and macrophages , Wiseman & Werb 2002. The stroma represents the major component of the adult human breast; during early reproductive life approximately 20% of breast tissue comprises epithelium, 20% fat and 60% connective tissue; the amounts of epithelium and connective tissue decline with age (Hutson et al 1985). It has been suggested that despite the lack of E receptors in human stromal cells, the stroma plays an important role in the control of hormone-mediated epithelial cell proliferation (Anderson et al 1998), through paracrine mechanisms (Shekhar et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mammographic density has been hypothesized to parallel age-related involution in the breast, which involves the reduction in size and number of acini per lobule as well as the replacement of the extralobular stroma by fat (42)(43)(44)(45). Both mammographic density and involution are influenced by reproductive factors and change with age, with the greatest changes after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…In parous women ages 35 to 45 years, it is estimated that the breast comprises 10% to 20% epithelium, with 60% to 80% fibroconnective tissue and 10% to 20% adipose tissue (39,40). The proportion of adipose tissue is likely to be higher in overweight and obese women, such as those who were eligible for this study.…”
Section: Discussionmentioning
confidence: 99%